Study Of Improvement in Small Fibre Neuropaty Using Diafoot Care Test in Patients with Controlled Diabetes Mellitus Who Presented to Dae Hospital - Sitaraman, Sridevi (Journal of Neonatal Surgery, 2025)
This study is to observe the improvement of small fiber neuropathy using dia foot care testing in patients with controlled diabetes mellitus who presented to our institution (DEPARTMENT OF ATOMIC ENERGY HOSPITAL ). Small fiber neuropathy is dangerous complication which can lead to foot ulcers, amputation and disability. The remission or cure of small fibre neuropathy is impossible so improvement can be attained with tight sugar control. So in this study we looked at the improvement of neuropathy in those whose hba1c levels and sugars well controlled and so early detection and management is important for the improvement of neuropathy symptoms in DM patients. Study methodology-This is a retrospective study done in our institution from February 2023-february 2025 of 100 patients after obtaining ethical clearance and informed consent from all patients who had symptoms of numbness, pricking sensation burning sensation in feet with DM on medications. Results-In our study we found that females <60 years are more affected with neuropathy .Hba1c > 7 was found in 32 females and 28 male patients. Risk factors like dyslipidemia, obesity, hypertension, family history were present in both sex out of which family history scored more to neuropathy. Hba1c levels(<7) with tight control of sugars with OHA and insulin after 2 years of treatment were found in 60 patients out of which neuropathy symptoms improved in 27 patients (2.7%) which is not significant as in line with national and international studies. Conclusion-Diabetic neuropathy testing using DIAFOOT care testing device is important screening tool for the management of neuropathy symptoms to prevent complications like foot ulcers, amputations, neuropathic pain and disability.